Provincial sociology as a new research direction - Sakovich, Anzhela Yu. (Journal of the Belarusian State University. Sociology, 2024)
A new research area is being represented – the provincial sociology. It is noted that in the near future, rural settlements of Belarus will not be able to provide the domestic agricultural sector with labour resources, due to a decrease in the number of inhabitants. A new approach to solving the problem of staffing the agro-industrial complex is proposed, involving the use of labour resources not only in the village, but also in the province. Based on the analysis of the concept of «province» and a review of the results of empirical sociological studies devoted to the study of the Belarusian and Russian provinces, the scientific direction «provincial sociology» is described, its object and subject are determined. It is concluded that rural development is a priority area of the province’s sociology. An effective solution in this area can be the creation of modernised agricultural holdings equipped with modern equipment and using the latest technologies. This will allow attracting specialists to rural areas who are ready to come to work daily from the nearest provincial cities.
Keywords: provincial sociology; provincial community; rural area; agro-industrial complex; labour resources